(NoSNOWY ^ISLENNYH METODOW (B:s (Nu^EBNOE POSOBIE (B/s - (NtUR^AK(B, (NlEONID iWANOWI^s; (N}ENNIKOW(B, (Nw(B.(Nw(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1987)
(NpREDM(B. (NUKAZ(B.: (NS(B. 312-318s
(NbIBLIOGR(B.: (NS(B. 309-311 (56 (NNAZW(B.)s
Keywords: (NkOMBINATORNYJ ANALIZ(B. (NtEORIQ wEROQTNOSTEJ(B. (NtEORIQ MNOVESTWs